The success of learning volleyball lower passing using modified sponge balls in elementry school - Rifaldy, Muhammad Alfian; Hadi, Santika Rentika (Universitas Suryakancana, 2025)
This study aims to determine the success of learning volleyball lower passing using a modified ball made from sponge for fifth grade students of SDN Bangsri Sukodono. A quantitative research method with a two-group pretest and posttest design was used, dividing the subjects into experimental (sponge ball) and control (regular volleyball) groups. The research instrument was a lower passing test with an indicator of directing the ball within 60 seconds. Results showed a significant effect of using sponge balls (significance value of 0.000) compared to regular balls (0.056), proving their effectiveness in increasing student success. In addition, sponge balls are also considered safer and more comfortable to use, thus supporting a more optimal learning process. In conclusion, sponge balls not only overcome facility limitations, but also increase interest in learning, reduce the risk of injury, and encourage active student participation, making them an effective alternative for learning basic volleyball techniques in elementary schools. These findings support sponge ball as a safe, cheap, and effective learning medium, while reducing the risk of injury. It is recommended that coaches and students implement training programs using sponge balls while still paying attention to the principles of training according to player characteristics.